Efficiency of Public Educational Expenditure in China - Zhiqian Yu; Ning Zhu; Yuan Zheng (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2013)
The study investigates the efficiency of local public educational expenditure of 31 provinces in China during 2005-2010, using the Slack-based Measurement (SBM) directional distance function. The results show that public educational expenditure is the most efficient in eastern China, followed by middle and western areas. The inefficiency can be explained mostly by the number of master graduates, while the impacts of the number of undergraduates and graduates from secondary school are also significant. Additionally, bootstrap method is applied to explore the contextual factors influencing the efficiency. The results suggest that economic development and urbanization process increase the efficiency, while the state-owned industry obstructs the development.
hdl:10398/8762
Keywords: 330; Public Educational Expenditure; Efficiency; Slack-based Measurement Directional Distance Function; Bootstrap; Bildungsfinanzierung; Bildungsabschluss; Räumliche Verteilung; China